Enhancing mathematical reasoning: role of the search, solve, create, and share learning - Putra, Fredi Ganda; Saregar, Antomi; Diani, Rahma; Misbah, Misbah; Widyawati, Santi; Imama, Khoirunnisa (Journal of Education and Learning (EduLearn), 2024)
The capacity for mathematical reasoning, pivotal in grasping core math concepts, directly shapes a student's success in their mathematical studies. This study aimed to detail and analyze how the search, solve, create, and share (SSCS) instructional framework impacts mathematical reasoning skills within the context of linear equations. We adopted a quasi-experimental research approach using a non-matching control group design. To gather data on mathematical reasoning proficiency, a validated and reliable essay-type test was employed. Data collection on mathematical reasoning abilities used an essay test instrument that has been valid and is reliable. This research involved 102 eighth grade students whereby they were selected by using a purposive sampling. o measure and describe the effect size, we utilized a specific method, yielding a result of 0.97. The t-test was employed to assess the influence of the SSCS learning model, and the significance value obtained was less than 0.05. The effect size, as determined, stands at 0.97, suggesting a substantial impact. The t-test results underscore a significant relationship between the SSCS learning model and the enhancement of mathematical reasoning abilities. This research delineates a framework for employing the SSCS model to enhance students' mathematical reasoning capabilities. It is evident that such reasoning abilities play a pivotal.